2015
DOI: 10.3126/jpahs.v1i2.16644
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-pathological characteristics of colorectal carcinoma at university teaching hospital, Nepal

Abstract: Introductions: Colorectal cancer is a major health problem in developing countries. The purpose of this study was to analyze the clinico-pathological characteristics of colorectal carcinoma at Patan hospital, Nepal.Methods: A retrospective chart review was done for patients operated for colorectal carcinoma at Patan Hospital from May 2004 to April 2012. Demographic information, chief complains, site of primary cancer, and histological types were analyzed.Results: There were 73 patients (37 males and 36 females… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 8 publications
(11 reference statements)
2
7
0
Order By: Relevance
“…Colorectal carcinoma was found to be more common among the age group of 51-60 years which was similar to the findings of a study done by Shah S et al 14 It is a matter of great concern that out of all colorectal cancers, 22.6% cases were found below 40 years which was 28.77% in a study of Shah et al 14 Malignancy was found to be more prevalent among male with M: F ratio of 1.6:1. The finding of Kansakar et al 15 was found to be 4:3 however, it was found to be equal in as study done by Shah S et al 14 and Khan MR et al 16 Stomach was found to be the second most commonly involved site comprising 28.6% however it was only 19.2% and 15.9% in a study done by Mohammad AM et al 17 and Jose L et al 18 respectively. Gastric carcinoma was found to be slightly more prevalent among male with M: F ratio of 1.4:1 but it was found to be 3:1 in a study done by Mohammad AM et al 17 Regarding age involvement, the finding of Mohammad AM et al 17 is similar to our finding as Gastric carcinoma was found to be less prevalent below 50 years (13.6%).…”
Section: Discussionsupporting
confidence: 90%
“…Colorectal carcinoma was found to be more common among the age group of 51-60 years which was similar to the findings of a study done by Shah S et al 14 It is a matter of great concern that out of all colorectal cancers, 22.6% cases were found below 40 years which was 28.77% in a study of Shah et al 14 Malignancy was found to be more prevalent among male with M: F ratio of 1.6:1. The finding of Kansakar et al 15 was found to be 4:3 however, it was found to be equal in as study done by Shah S et al 14 and Khan MR et al 16 Stomach was found to be the second most commonly involved site comprising 28.6% however it was only 19.2% and 15.9% in a study done by Mohammad AM et al 17 and Jose L et al 18 respectively. Gastric carcinoma was found to be slightly more prevalent among male with M: F ratio of 1.4:1 but it was found to be 3:1 in a study done by Mohammad AM et al 17 Regarding age involvement, the finding of Mohammad AM et al 17 is similar to our finding as Gastric carcinoma was found to be less prevalent below 50 years (13.6%).…”
Section: Discussionsupporting
confidence: 90%
“…of 51.76 ± 15.78 years. These findings were similar to findings of Vaidya et al 3 , Rajbhandari et al 2 and Shah et al 14 where age ranged from 16 to 87 years and mean age was 51.80, 52 and 53 years respectively. Males were more commonly affected than females with a male female ratio of 1.7:1.…”
Section: Original Research Article Polyps and Cancer Of Colorectumsupporting
confidence: 91%
“…Males were more commonly affected also in studies conducted by Vaidya et al 3 , Shrestha et al 15 and Ibrahim et al 16 with male female ratio of 3:1, 1.4:1 and 1.5:1 respectively. However, females were slightly more commonly affected in studies conducted by Shah et al 14 and Rajbhandari et al 2 with male female ratio of 0.9:1 and 1:1.08 respectively. 64.2% cases were seen in distal colon and 35.8% cases were seen in proximal colon which was similar to studies of Rajbhandari et al 2 and Vaidya et al 3 51.3% cases of malignancy were seen in rectum.…”
Section: Original Research Article Polyps and Cancer Of Colorectummentioning
confidence: 83%
See 1 more Smart Citation
“…[3][4][5][6][7] Few studies in Nepal have also showed the increasing overall trends in CRC in young population. [8][9][10][11] The main objective of our study was to estimate the burden of CRC among young. The secondary objective was to highlight the need of awareness among medical personnel and general population regarding need of earlier screening strategies to prevent over all deaths from CRC in our country.…”
Section: Introductionmentioning
confidence: 99%